Fragmentation of Authority in National Cyber Defense A Legal Analysis of Overlapping Inter-Agency Authority and the Urgency of Integrated Command - Restu Putri Pamungkas; Bambang Kustiawan; Asep Adang Supriyadi; Guntur Eko Saputro (UNIVERSITAS PAKUAN, 2026)
The evolution of cyberspace as the fifth domain of warfare has transformed the national defense landscape, where hybrid threats can now disrupt sovereignty without physical war declarations. Indonesia responds to this challenge through the Total People's Defense and Security System (Sishankamrata) doctrine, yet its implementation is hindered by acute institutional fragmentation. This study aims to analyze the implications of regulatory disharmony on strategic defense effectiveness and formulate an ideal legal construction for national cyber governance. Using normative legal research methods with statutory and conceptual approaches, this study finds that current sectoral regulations create legal antinomy between defense mandates (Military/TNI), law enforcement (Police/Polri), and administrative security (National Cyber and Crypto Agency/BSSN). An asymmetry of authority is identified where BSSN, as the coordinator, is based only on a Presidential Regulation, lacking operational coercive power over institutions established by Law. The absence of legal escalation mechanisms in the